Pengaruh Keamanan, Kenyamanan, Kualitas dan Fitur Aplikasi Terhadap Kepuasan Nasabah Bank BPRS Dinar Ashri Pengguna Mobile Banking - Angga Lawang Sani; Muhajirin Muhajirin; Ovriadin Ovriadin (Institut Nalanda, 2024)
This study aims to analyze the influence of security, convenience, quality, and application features on customer satisfaction of Bank BPRS Dinar Ashri mobile banking service users. In today's digital era, mobile banking is one of the important services offered by banks to facilitate customer transactions. This study uses a quantitative approach with a survey method through questionnaires distributed to mobile banking users. The results of the analysis show that the security, convenience, quality, and features of the application have a significant influence on customer satisfaction. From the results of this study, banks can identify factors that need to be considered to increase customer satisfaction with mobile banking services.